The Impact of Spiritual Emotional Freedom Technique (SEFT) on Adolescent Nicotine Dependence: A Quasi-Experimental Study - Linda Linda; Idramsyah idramsyah; Wisuda Andeka Marleni (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Adolescent smoking remains a major public health concern in Indonesia, with increasing rates of nicotine dependence and limited effectiveness of existing cessation strategies. Culturally relevant, low-cost, and non-pharmacological interventions are needed, particularly for adolescents with strong religious backgrounds. The Spiritual Emotional Freedom Technique (SEFT), which integrates emotional regulation, acupressure tapping, and spiritual affirmation, may offer a holistic approach to smoking cessation. This study aimed to evaluate the effectiveness of SEFT in reducing nicotine dependence among adolescent smokers. Methods: A quasi-experimental pretest–posttest control group study was conducted in Bengkulu City, Indonesia, involving 60 Muslim adolescent smokers aged 18–25 years who intended to quit smoking. Participants were consecutively recruited and allocated to an intervention group (SEFT; n=30) or a control group (hypnotherapy without tapping; n=30). SEFT was delivered individually for approximately 10 minutes per session over three consecutive days. Nicotine dependence was assessed using the Fagerström Test for Nicotine Dependence (FTND) at baseline and one week post-intervention. Data were analysed using the Wilcoxon signed-rank test and Mann–Whitney U test. Results: The intervention group showed a significant reduction in FTND scores from pretest to posttest (p=0.001), whereas no significant change was observed in the control group (p=0.177). Post-intervention FTND scores differed significantly between groups (p<0.001), indicating a substantial effect of SEFT in reducing nicotine dependence. Conclusion: SEFT was effective in reducing nicotine dependence among adolescent smokers and demonstrated greater benefits than hypnotherapy alone. SEFT represents a culturally congruent, low-cost complementary intervention with potential for integration into school- and community-based smoking cessation programs in Indonesia.